Painful cutaneous laser stimuli induce event-related oscillatory EEG activities that are different from those induced by nonpainful electrical stimuli - Chien, J. H. (American Physiological Society, 2014)
The non-phase-locked EEG response to painful stimuli has usually been characterized as decreased oscillatory activity (event-related desynchronization, ERD) in the alpha band. Increased activity (event-related synchronization, ERS) in the gamma band has been reported more recently. We have now tested the hypothesis that the non-phase-locked responses to nonpainful electric cutaneous stimuli are different from those to painful cutaneous laser stimuli when the baseline salience of the two stimuli is the same and the salience during the protocol is modulated by count laser and count electric tasks. Both of these stimuli were presented in random order in a single train at intensities that produced the same baseline salience in the same somatic location. The response to the laser stimulus was characterized by five windows (designated windows I–V) in the time-frequency domain: early (200–400 ms) and late (600–1,400 ms) delta/theta ERS, 500–900 ms alpha ERD, 1,200–1,600 ms beta ERS (rebound), and 800–1,200 ms gamma ERS. Similar ERS/ERD windows of activity were found for the electric stimulus. Individual participants very commonly had activity in windows consistent with the overall analysis. Linear regression of ERS/ERD for parietal channels was most commonly found for sensory (pain or unpleasantness)- or attention (salience)-related measures. Overall, the main effect for modality was found in window I-delta/theta and window V-gamma, and the Modality with Task interaction was found in all five windows. All significant interaction terms included Modality as a factor. Therefore, Modality was the most common factor explaining our results, which is consistent with our hypothesis.